Paul Virilio, l’accident comme ressource immatérielle - Jean Richer (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Following Paul Virilio's thinking on the integral accident, this article presents the accident, in all its forms, as being consubstantial with architecture and urbanism. By observing how the accident has been able to tyrannize material resources in the art of building, and how it finds a definitive expression in ruin, the article attempts to form a new definition of accident as an immaterial resource in the face of ever-increasing risks. Therefore, thinking of ruin in reverse in the architectural process would open the way to an economy of material resources.